Pathogen hijacks focal adhesion signaling by a T3SS effector CteX - Xing Pan; Yanbo Zhao; Jiwei Luo; Lili Ding; Lina Ma; Yanxin Li; Juan Xue; Xinyuan Tao; Songying Ouyang; Shan Li (Proceedings of the National Academy of Sciences, 2026)
Infections by Gram-negative pathogens like Salmonella and Shigella rely on type III secretion system (T3SS) effectors. While the opportunistic pathogen Chromobacterium violaceum encodes a crucial T3SS (Cpi-1/-1a), its full effector repertoire remains undefined. Here, we performed a comprehensive proteomic analysis of the C.v. Cpi-1/-1a T3SS secretome. Our analysis not only confirmed known effectors but also unveiled CteX, an effector with no prior functional annotation. Structural determination revealed that CteX adopts a papain-like fold, and functional studies demonstrated that it acts as a cysteine protease that specifically cleaves the focal adhesion adapter protein Paxillinα. This proteolytic activity triggers the collapse of focal adhesions and actin cytoskeleton. CteX-mediated cytoskeletal remodeling limits excessive invasion of epithelial cells by C. violaceum , which could otherwise lead to widespread cell death and premature bacterial exposure. Further, animal infection models confirm that CteX is essential for the virulence and sustained colonization of C. violaceum . Thus, we identify CteX as a T3SS effector that orchestrates bacterial persistence through the unexpected proteolytic targeting of host focal adhesions.